"Salt in the Wound": Safety Net Clinician Perspectives on Performance Feedback Derived From EHR Data. Issue 1 (January 2017) - Bunce, Arwen E.; Gold, Rachel; Davis, James V.; Mercer, MaryBeth; Jaworski, Victoria; Hollombe, Celine; Nelson, Christine
Abstract : Electronic health record (EHR) data can be extracted for calculating performance feedback, but users' perceptions of such feedback impact its effectiveness. Through qualitative analyses, we identified perspectives on barriers and facilitators to the perceived legitimacy of EHR-based performance feedback, in 11 community health centers (CHCs). Providers said such measures rarely accounted for CHC patients' complex lives or for providers' decisions as informed by this complexity, which diminished the measures' perceived validity. Suggestions for improving the perceived validity of performance feedback in CHCs are presented. Our findings add to the literature on EHR-based performance feedback by exploring provider perceptions in CHCs.